Safety of house dust mite subcutaneous immunotherapy in preschool children with respiratory allergic diseases - Yaqi Yang; Dongxia Ma; Nan Huang; Wenjing Li; Qing Jiang; Yin Wang; Xiaolong Wang; Lin Yang; Rongfei Zhu (BMC, 2021)
Abstract Background Allergen immunotherapy (AIT) is the only causal therapy for IgE-mediated allergy. There is less evidence about the safety and efficacy of AIT especially subcutaneous immunotherapy (SCIT) in children under 5 years old. We aimed to investigate the side effects and associated risk factors of house dust mite (HDM) SCIT in preschool children with respiratory allergic diseases. Methods The preschool children who had HDM-related allergic rhinitis with/without asthma were enrolled and undergone standardized HDM SCIT in our department from June 2013 to December 2019. Local reactions (LRs) and systemic reactions (SRs) were recorded and categorized according to World Allergy Organization recommendations. Demographic data and other therapeutic-related parameters were also recorded to investigate potential risk factors for these side effects. Results A total of 91 children (60 boys, 65.93%; 31 girls, 34.07%; mean age 4.13 years old) were included in the study. Among the 91 patients, 3109 SCIT injections were recorded, 62/91 (68.13%) experienced 186 immediate LRs, 4 /91(4.40%) experienced 6 delayed LRs, 11/91 (12.09%) children experienced 44 immediate SRs, 21/44 (47.73%) were grade 1 SRs, 21/44 (47.73%) were grade 2, 2/44 (4.55%) were grade 3, no grade 4 or 5 SRs occurred. Furthermore, 1/91 (1.10%) experienced 1 delayed SRs, manifested by urticaria 2 days later after allergen injection. 9/91 (9.89%) experienced 2 or more times SRs. Multivariable logistic regression analysis showed BMI (OR 1.506; 95%CI 1.091 to 2.079; p < 0.05) and sIgE against HDM (OR 1.497; 95%CI 1.082 to 2.071; p < 0.05) were risk factors for LRs. No variable was found to correlate with SRs (all p > 0.05). Conclusions HDM subcutaneous immunotherapy is considered to be safe in preschool children with respiratory allergic diseases. Higher BMI and HDM sIgE level in children are risk factors for developing LRs. The incidence of SRs and the rate of severe SRs are low in preschool children.